Software architecture of an interface for three-dimensional collision handling in maritime Virtual Environments. (August 2015) - Varela, José; Soares, C Guedes
This paper presents the software architecture of an interface for real-time three-dimensional (3D) collision detection and determination in a maritime Virtual Environment. Interface classes, attributes and functions to compute the collision point, the moment of impact, and the local velocity and normal vectors of the surfaces at the collision point are described. If a physics application programming interface is available, these values can be used to estimate the objects' responses to the collision. Within the scope of this work, a wrapper was developed and integrated in a 3D Ship Simulator prototype system.